Space-time coding for MIMO systems with co-channel interference. - Arunachalam, A.
We consider the design of space-time codes for multiple-input multiple-output (MIMO) systems operated in the presence of co-channel interference (CCI). Based on the pairwise probability of error analysis, we develop a new design criterion that determines the code robustness to CCI (CCI diversity gain). We further develop an algebraic framework for constructing space-time codes that jointly optimize the fading and CCI diversity gains. The proposed framework is general for arbitrary numbers of transmit antennas and quadrature amplitude modulation constellations. Numerical results that quantify the performance gains offered by the proposed techniques are also presented.
Keywords: MIMO system; Cochannel interference; Error analysis; Multiple-input multiple-output.; Pairwise probability; Quadrature amplitude modulation constellation; Space-time coding; Transmit antenna